Attitude of Physiotherapists Towards Dealing Subjects with Mental Illness (Indian Journal of Forensic Medicine & Toxicology, 2021)
INTRODUCTION: The concept of mental health receives negative opinions and are stigmatized in publicdespite evidence of importance of mental health for social and human capital. It is important that thereshould be a multidisciplinary approach when it comes to rehabilitation of patients with Mental Illness thanconcentrating only in the psychiatry aspect. Patients with Mental Illness can also suffer from physical healthrelated co-morbidities in which physiotherapy can play a role in improving the lifestyle. OBJECTIVE:The aim of the study was to assess the attitude of physiotherapists towards subjects with mental illness.METHODS: A non-experimental study of convenient samples was carried out among 100 physiotherapists.Data collection was performed using the questionnaire MICA-4(Mental Illness Clinicians Attitude Scale).The questionnaire includes 16 items and has a 6- point Likert-type response format. Each item has itsown definite score. A higher score depicts negative attitude and a lesser score shows a positive attitude.RESULTS: The data was analysed using SPSS statistics version 23. The results revealed that 73% of thesubjects had neutral attitude towards dealing individuals with any form of mental illness. CONCLUSION:The neutral attitude recorded is indicative of lack of exposure of physiotherapists in the field of psychiatry.Training at an early stage can be beneficial for future therapists to deal in a better way with mental illnesspatient having physical health problems. It is important to promote this area of specialisation both for clinicaland research studies in order to implement strategies to avoid stigmatisation.
Keywords: Attitude, Mental illness, Mental disorder, Mental Illness Clinician Attitude scale, Physiotherapist.